Referências ao teatro nas Filípicas de Cícero e suas implicações para o ethos de Marco Antônio: a atriz de mimo Volumnia Cytheris.: References to theater in Cicero's Philipics and theirs implications to Mark Anthony's ethos: the mimo actress Volumnia Cytheris - Abreu, Bruna Fernanda (Rónai – Revista de Estudos Clássicos e Tradutórios, 2018)
O principal objetivo de nosso trabalho é expor e analisar alguns trechos das quatorze Filípicas de Cícero para verificar como as referências à atriz de mimo Volumnia Cytheris aparecem neles e de que modo colaboram para a construção da imagem de Marco Antônio como um personagem cômico ele próprio. Abstract It’s evident the slanderous content of Cicero’s Philipics against Mark Antony, since in these speeches the speaker attacks the private and political life of his adversary. The main objective of our paper is to study a certain aspect of Cicero’s strategy presenting and analysing some sections from Cicero’s fourteen Philippics in order to verify from them how references to mimo actress Volumnia Cytheris appear and what they mean for the construction of Mark Antony’s image as a comic character. Keywords: Cicero; Philippics; theater; Mark Antony; Volumnia Cytheris